Non-Roman Language Cataloging in Bulk: A Case Study of Japanese Language Materials. Issue 2 (17th February 2017) - Nakano, Hikaru
ABSTRACT: Aozora Bunko is a Japanese full-text database of works that are in the public domain. The University of Florida libraries modified the approximately 5, 000 Japanese language records into English language MARC records compatible with Resource Description and Access (RDA), and added those records to OCLC and their integrated library system (ILS). Thus, this analytical cataloging project makes it possible to introduce more users to these Japanese anthologies in full text. This article describes the methods used to convert spreadsheet data that contains non-Roman characters into MARC records and indicates the possibilities that are applicable to similar projects in other non-Roman languages.